Nilai-nilai Kurikulum Cinta dalam Surah Ali Imran Ayat 31 - Muhammad Rafi; Ahmad Siddiq; Krenniti Sundari; Izzatussyakira Izzatussyakira; Mohammad Al Farabi (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2025)
Moral degradation and the loss of compassionate values in educational institutions, especially for students, are serious challenges in the world of education and religion. Education that has tended to emphasize cognitive aspects has not fully succeeded in forming character, intellectual, spiritual and also emotional in students as a whole. The research data collection technique uses a qualitative approach with library research data analysis, namely using literature in the form of books and journals. This study aims to explore the love curriculum in Surah Ali Imran verse 31, find out the meaning of love according to the perspective of the Quran in Surah Ali Imran verse 31, and develop a model of characteristic education not only from cognitive but also from moral values in spiritual, intellectual and emotional. The results of the study show that the value of the love curriculum in Surah Ali Imran verse 31 has a similar continuity, namely the same meaning in the form of values for mutual affection, love and education not only from cognitive development but also on morals or character. The conclusion is that the love curriculum has religious values with the argument of Surah Ali Imran verse 31 which makes educational development not only intellectual, but also spiritual and emotional, etc.